Rekayasa Teknologi Konstruksi dan Manufaktur: Optimalisasi Material dan Strategi Teknikal dalam Infrastruktur Sumatera Utara - Abidan Napitupulu; Andi Saputra; Mananda Ture Siburian (ELASTICITY: Journal of Applied Engineering Science, 2025)
Structural performance in a variety of loading scenarios is an important aspect of civil engineering. This study compares the capacity of the structure based on existing conditions and simulation results using the ATC-40 and FEMA 356 methods. The main parameters analyzed include drift ratio, base shear, and displacement. The data sources used in this study consist of three main aspects, namely field and laboratory measurements. The data analysis in this study uses a combination of quantitative methods and numerical simulations. The results of the analysis showed that the drift ratio decreased from 1.5% in the existing conditions to 1.2% and 1.3% in the ATC-40 and FEMA 356 simulations. The base shear is also reduced from 500 kN to 480 kN and 470 kN, while the displacement is reduced from 35 mm to 32 mm and 30 mm. In addition, analysis of the stress distribution of various materials such as SS304L, NiCr, and 20% HTM showed significant differences in tensile strength, modulus of elasticity, and elongation. This study provides important insights for designing safer and more efficient structures to withstand dynamic loads